Evaluating the Quality and Added Value of Durian Peel Briquettes Using Tar Waste as Adhesive - Fahrulsyah, Fahrulsyah; Ningtyas, K R; Agassi, T.N; Harahap, M. P. M (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Durian peel has a cellulose content that reaches 64.51%. The high cellulose value in durian peel has the potential to be an energy source for making bio-briquettes. Charcoal biobriquettes require adhesive to hold the charcoal powder together, affecting the calorific value. In this research, the adhesive used was tapioca flour and tar. To measure the quality of durian peel briquettes, the water content, ash content, calorific value, and added value of the product were tested. The research showed that durian peel briquettes treated with variations in tapioca flour and tar adhesive (3:1) had good quality. This can be seen from the water content of 9.41% and the ash content of 13.6%; these values ??are still by the Minister of Energy and Mineral Resources Regulation No. 47 of 2006. The calorific value of the briquette product is 9694.53 cal/g and entered into SNI standards. Calculation or analysis of product-added value is calculated using the Hayami method. IDR is the added value from the one-time processing of durian peel bio briquette production with 30 kg of raw materials. IDR. 7000/kg. Based on the added value ratio when connected to Hubeis theory, the added value of this biobriquette product is in the high category (>40%).